Trust within the Organizations of the New Economy: an Empirical Analysis of the Consequences of Institutional Uncertainty - Marco Tulio F. Zanini; Edward J. Lusk; Birgitta Wolff (RAC: Revista de Administração Contemporânea, 2009)
This study investigates the effects of different institutional frameworks on the levels of trust within hierarchies. Following the insight into the changing of labour contracts provided by New Economy theorists and International Labour Organization [ILO] reports, this study investigates the possible differences in the levels of trust between two paradigms: the Old Economy and the New Economy. We argue that singular institutional changes which better characterize the New Economy in the form of environmental uncertainty set considerable constrains on trust development. By approaching trust as a dependent variable in a cross-industrial comparison, a questionnaire survey was carried out in Brazil accessing the levels of trust within seven Brazilian private companies. From the literature review and empirical observation of the reality of these organizations, companies were identified and classified into different groups. The study concludes that relative high institutional uncertainty considerably limits the development of trust levels within those companies operating in the New Economy.